Randomized controlled trial of Phyllanthus niruri Linn extract - Patria Vittarina Sarisetyaningtyas; Sri Rezeki Hadinegoro; Zakiudin Munasir (Indonesian Pediatric Society, 2006)
Background Clinical benefits of antiviral treatment in childrenexperience varicella without complications, remains controversial.Phyllanthus niruri Linn extract as a natural medicine is used toincrease cellular and humoral immunity.Objective To determine the efficacy and safety of Phyllanthusniruri Linn extract in the treatment of varicella in children comparedto placebo.Methods This was a double-blind randomized controlled trial onchildren ages 2-14 years who experienced varicella without com-plications. Subjects were randomly assigned to receive eitherPhyllanthus niruri Linn extract syrup (5 mg/5ml, 3 times daily) orplacebo. Efficacy was measured by calculating the number of pap-ules and crusts after taking the extract for 4 days of administration.A five-day monitoring sheet to record daily follow up and adverseeffects of the subjects were given to their parents.Results Efficacy of Phyllanthus niruri Linn measurement basedon no more new papules occurred at the five-day monitor was de-tected in 46 subject (51.1%) of the Phyllantus niruri Linn groupcompared to the placebo group (P=0.723). Meanwhile, the differ-ence of efficacy based on time of crusts disappear in Phyllanthusniruri Linn and placebo group were 22 subjects (43.1%) and 15subject (30.0%), respectively (P=0.053). This finding proved haveclinical benefit (NNT=7.6).Conclusion There was no significant difference between the ef-ficacy of Phyllanthus niruri Linn and placebo in terms of the pre-vention appearing new papules and crusts. However, clinicallyPhyllanthus niruri Linn accelerates appearing and aborting crustcompared to placebo